2018
DOI: 10.1017/s2045796018000458
|View full text |Cite|
|
Sign up to set email alerts
|

Reducing mental health-related stigma in primary health care settings in low- and middle-income countries: a systematic review

Abstract: More rigorous trials are needed in LMICs to test interventions that target discriminatory behaviours in relationship with patients. Cultural adaptation of stigma interventions and structural/institutional factors should be more explicitly addressed in such trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 37 publications
3
49
1
Order By: Relevance
“…The same result was found in a previous systematic review on anti-stigma interventions with health professionals in LMICs (Heim et al ., 2018). Measuring behavioural outcomes is a challenge, particularly in resource-strained contexts, because it requires time and human resources to assess students’ skills in their contact with patients (Nortje and Seedat, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The same result was found in a previous systematic review on anti-stigma interventions with health professionals in LMICs (Heim et al ., 2018). Measuring behavioural outcomes is a challenge, particularly in resource-strained contexts, because it requires time and human resources to assess students’ skills in their contact with patients (Nortje and Seedat, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with those which have shown that attitudes can be improved following education aimed at reducing stigma [39,40]. A systematic review of reducing mental health stigma among primary health care settings in LMICs demonstrated that education could have important impacts on stigma such as reducing stigmatizing attitudes [41]. Additional evidence indicates that education can positively change attitude, while there is less evidence for improving knowledge [42].…”
Section: Discussionsupporting
confidence: 90%
“…27 In China, mental disorders are also associated with stigma, and patients with mental disorders are likely to have negative experiences and discrimination when receiving health services. 49,50 However, statistical differences of expectations between patients from the MHD and ED were only detected in two domains in our study. Potential explanations for that could be that almost half of the patients from the MHD in this study were diagnosed with depression and/or anxiety.…”
Section: Discussioncontrasting
confidence: 78%